2023
DOI: 10.1097/apo.0000000000000590
|View full text |Cite
|
Sign up to set email alerts
|

Latest Development in Extended Depth-of-Focus Intraocular Lenses: An Update

Abstract: In recent years, there has been an overwhelming influx of different types of intraocular lenses (IOLs) as treatment for presbyopia. The extended depth-of-focus (EDOF) technology creates a single elongated focal point to enhance depth of focus, in contrast to the multiple foci of multifocal (MF) lenses. In this way, the EDOF lenses aim to reduce photic phenomena, glare, and halos, which have been reported in MF IOLs. A potential disadvantage of this is a blur due to decreased retinal image quality when the amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 102 publications
(282 reference statements)
2
19
0
Order By: Relevance
“…Most of these patients did not consider the photic phenomena disturbing to their daily life activities. Previous studies reported a rate of photic phenomena ranging between 14% and 80% in patients implanted bilaterally with EDOF IOLs 11,19–22 . A low percentage of photic phenomena was documented in both groups in our study.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Most of these patients did not consider the photic phenomena disturbing to their daily life activities. Previous studies reported a rate of photic phenomena ranging between 14% and 80% in patients implanted bilaterally with EDOF IOLs 11,19–22 . A low percentage of photic phenomena was documented in both groups in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies reported a rate of photic phenomena ranging between 14% and 80% in patients implanted bilaterally with EDOF IOLs. 11,[19][20][21][22] A low percentage of photic phenomena was documented in both groups in our study. The high variability in the literature could be explained by the lack of standardization in the different types of questions targeting this issue, which could influence the percentage of reported symptoms.…”
Section: Discussionsupporting
confidence: 45%
“…The way they achieve this focus extension is purely refractive, by means of the higher-order asphericity of the anterior surface, characterized by continuous power change from the periphery to the center of the lens. 15,18 The rationale of their introduction rests on the issues related to the photic phenomena, including glare, halos, and contrast sensitivity reduction, that are reported to occur after the implantation of diffractive multifocal optical systems. 4,[19][20][21] Despite being this a general and vague theme, it cannot be denied that it still remains a controversial concern for surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…6,16 Given this evidence, enhanced monofocal IOLs might thus be considered as a hybrid system (for the purpose named "mono-EDOF" [extended depth of focus]), which retains the optical quality of monofocal but augmented with a focus extension. 15,18 It must be evidently disclosed that uncorrected near vision goes beyond true expectations, and patients shall be warned about the need for correction while reading or performing other near activities for long.…”
Section: Discussionmentioning
confidence: 99%
“…They are made of a copolymer of HEMA (hydrophilic component) and EOEMA (hydrophobic component), which provides a good trade-off between elasticity and mechanical resistance. In addition, an optimized distribution of positive and negative spherical aberrations provides continuous focus from far to near distance [ 14 ]. Figure 2 reports the basic principle of Mini Well and Mini Well Proxa EDOF-IOLs, and some other details will be reported in the following sections.…”
Section: Introductionmentioning
confidence: 99%